2021
DOI: 10.1186/s12884-020-03536-0
|View full text |Cite
|
Sign up to set email alerts
|

Maternal post-traumatic stress and depression symptoms and outcomes after NICU discharge in a low-income sample: a cross-sectional study

Abstract: Background Having a preterm newborn and the experience of staying in the neonatal intensive care unit (NICU) has the potential to impact a mother’s mental health and overall quality of life. However, currently there are few studies that have examined the association of acute post-traumatic stress (PTS) and depression symptoms and infant and maternal outcomes in low-income populations. Design/ methods In a cross-sectional study, we examined adjusted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…Eleven studies, published in 14 records, involved mothers and fathers; 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 one study involved fathers only [60] and the remaining 23 studies, reported in 26 records, involved mothers. 27 , 28 , 30 , 31 , 32 , 34 , 38 , 39 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven studies, published in 14 records, involved mothers and fathers; 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 one study involved fathers only [60] and the remaining 23 studies, reported in 26 records, involved mothers. 27 , 28 , 30 , 31 , 32 , 34 , 38 , 39 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 …”
Section: Resultsmentioning
confidence: 99%
“…Clinical interview was used in two studies, 46 , 54 clinical review of self-report scales was used in one study, published in three records, 38 , 39 , 62 and self-report scales were used in 32 studies, published in 36 records. 27 , 28 , 30 , 31 , 32 , 34 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 63 , 64 , 65 , 66 , 67 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 Seven different self-report scales were used, most commonly the Perinatal Post-traumatic Stress Disorder Questionnaire (PPQ). Cut-off points varied across studies, even when the same measure was used.…”
Section: Resultsmentioning
confidence: 99%
“…Yet, our results may represent general variations in parent experiences since it is known that a NICU hospitalization is traumatic and overwhelming for families. 17,24,38,40 Healthcare providers working with families in the NICU must consider the additional challenges that the COVID-19 pandemic has brought to family life. Our findings indicate that families may be uniquely affected by the pandemic and its sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the COVID-19 pandemic, evidence showed that families are noticeably affected by their infant's health crisis and NICU hospitalization. 17,18 Parents of verypreterm infants are more likely to report higher rates of anxiety and depressive symptoms along with poorer family functioning both during and after NICU hospitalizations. [19][20][21] Social isolation, disruption to family routines, and unpaid time off from work were associated with negative impacts on family life.…”
mentioning
confidence: 99%
“…The birth of a child with a medical condition that carries a risk of death, long-term health problems, or an uncertain prognosis is an extremely stressful experience for parents [ 3 ]. Parents of infants requiring neonatal intensive care unit (NICU) hospitalization are at risk for persistent anxiety, depression, post-traumatic stress and poor quality of life, which can adversely impact the long-term health and development of the child and family [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%